An Analysis of Translating Strategies on Apprenticeship Students’ Translation Products in Pikiran Rakyat Newspaper Company - Kaisan Rifki Al Maruf (Passage, 2015)
The research aims to discover the types of translation strategies which were found in apparenticeship students’ translation products and to assess the students’ English-Indonesian translation quality by asking five English students to rank the students’ translation products. This research employs the theory of translation strategy proposed by Vinay and Darbelnet (2000) and Sara Bani (2006). The criterias that are used to assess the apparenticeship students’ translation products are proposed by Barnwell (1980 as cited in Larson, 1984). Descriptive Qualitative study approach by Cresswell (2002), was used as the research design of the research. There are 172 selected phrases which were analyzed by the research. The result reveals that the most frequently used translation strategy is Calque (45.35%), then it was followed by Borrowing (29.65%), Adaptation (8.14%), Equivalence (6.40%), Substitution (4.66%), Generalization (2.33%), Transposition (1.74%), and Inclusion of Explanation (1.74%). The result also shows that (77.78%) of text was cut by the translators to eliminate the information that is too detail and unimportant, then to remove the information that had been covered by the previous sentences, and to cut the sensitive issue that may cause misconception to the readers. Most of participants thought that the translation products were good and understandable. However, the participants thought that the translation products are not natural since the translators used too much Calque translation strategy in translating the text.Keywords: translation strategies, translation quality, vinay and darbelnet (2000), Bani (2006)